Beispiel Nr: 01
$ \text{Gegeben:}\\\text{Oberfläche} \qquad O \qquad [m^{2}] \\ \\\text{Grundfläche} \qquad G \qquad [m^{2}] \\ \\ \text{Gesucht:} \\\text{Mantelfläche} \qquad M \qquad [m^{2}] \\ \\ M = O- 2\cdot G \\ \textbf{Gegeben:} \\ O=48m^{2} \qquad G=4m^{2} \qquad \\ \\ \textbf{Rechnung:} \\ M = O- 2\cdot G \\ O=48m^{2}\\ G=4m^{2}\\ M = 48m^{2}- 2\cdot4m^{2} \\ M=40m^{2} \\\\\\ \tiny \begin{array}{|l|} \hline O=\\ \hline 48 m^2 \\ \hline 4,8\cdot 10^{3} dm^2 \\ \hline 4,8\cdot 10^{5} cm^2 \\ \hline 4,8\cdot 10^{7} mm^2 \\ \hline 0,48 a \\ \hline 0,0048 ha \\ \hline 4,8\cdot 10^{-5} km^2 \\ \hline \end{array} \tiny \begin{array}{|l|} \hline G=\\ \hline 4 m^2 \\ \hline 400 dm^2 \\ \hline 4\cdot 10^{4} cm^2 \\ \hline 4\cdot 10^{6} mm^2 \\ \hline 0,04 a \\ \hline 0,0004 ha \\ \hline 4\cdot 10^{-6} km^2 \\ \hline \end{array} \tiny \begin{array}{|l|} \hline M=\\ \hline 40 m^2 \\ \hline 4\cdot 10^{3} dm^2 \\ \hline 4\cdot 10^{5} cm^2 \\ \hline 4\cdot 10^{7} mm^2 \\ \hline 0,4 a \\ \hline 0,004 ha \\ \hline 4\cdot 10^{-5} km^2 \\ \hline \end{array}$